Red Cells, Hemoglobin, Heme, Iron and Atherogenesis - Nagy, Em̋ke (2010)
OBJECTIVES: We have investigated whether red cell infiltration of atheromatous lesions promotes the later stages of atherosclerosis. METHODS AND RESULTS: We find that oxidation of ferro (FeII) hemoglobin in ruptured advanced lesions occurs generating ferri (FeIII) hemoglobin and via more extensive oxidation ferrylhemoglobin (FeIII/FeIV=O). The protein oxidation marker, dityrosine, accumulates in complicated lesions accompanied by the formation of crosslinked hemoglobin, a hallmark of ferrylhemoglobin. Exposure of normal red cells to lipids derived from atheromatous lesions causes hemolysis and oxidation of liberated hemoglobin. In the interactions between hemoglobin and atheroma lipids, hemoglobin and heme promote further lipid oxidation and subsequently endothelial reactions such as upregulation of heme oxygenase-1 and cytotoxicity to endothelium. Oxidative scission of heme leads to release of iron and a feed-forward process of iron-driven plaque lipid oxidation. The inhibition of heme release from globin by haptoglobin and sequestration of heme by hemopexin suppress hemoglobin-mediated oxidation of lipids of atheromatous lesions and attenuate endothelial cytotoxicity. CONCLUSIONS: The interior of advanced atheromatous lesions is a pro-oxidant environment in which erythrocytes lyse, hemoglobin is oxidized to ferri- and ferrylhemoglobin, and released heme and iron promote further oxidation of lipids. These events amplify the endothelial cell cytotoxicity of plaque components.